Use of magnetic field for controlling ice formation - Muhammad ‘Asyur Jumain (2019)
The behaviour of ferrofluid droplets under freezing conditions is investigated by quantifying parameters including freezing time, aspect ratio and the universality of the tip formation. We explored the behavioural differences between homogeneous and non-homogeneous ferrofluid solutions and prepared varying volumetric concentrations for each solution. Varying the homogeneity and concentration allow us to better understand underlying trends that govern the behaviour of these droplets during the freezing phenomenon. Our intention is to present potential ways of controlling and possibly altering the geometry of a frozen ferrofluid droplet and we aim to achieve it by incorporating a magnetic environment in our experiments.